Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 183173 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Bombus Latreille, 1802", "Geometry POLYGON((-164.53125 71.746431,-164.53125 9.795677,-38.671874 9.795677,-38.671874 71.746431,-164.53125 71.746431))" ] } The dataset includes 183173 records from 35 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0002201-150221044754056/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences